Potential applications of algae in the cathode of microbial fuel cells for enhanced electricity generation with simultaneous nutrient removal and algae biorefinery: Current status and future perspectives. (November 2019) - Nagendranatha Reddy, C.; Nguyen, Hai T.H.; Noori, Md T.; Min, Booki
Highlights: Current status and potentials of algae-cathode MFCs were comprehensively reviewed. Limitations and future perspectives of algae MFC for real applications was discussed. A closed-loop algae MFC system with biorefinery concept was presented. Abstract: Production of biofuels and other value-added products from wastewater along with quality treatment is an uttermost necessity to achieve environmental sustainability and promote bio-circular economy. Algae-Microbial fuel cell (A-MFC) with algae in cathode chamber offers several advantages e.g. photosynthetic oxygenation for electricity recovery, CO2 -fixation, wastewater treatment, etc. However, performance of A-MFC depends on several operational parameters and also on electrode materials types; therefore, enormous collective efforts have been made by researchers for finding optimal conditions in order to enhance A-MFC performance. The present review is a comprehensive snapshot of the recent advances in A-MFCs, dealing two major parts: 1) the power generation, which exclusively outlines the effect of different parameters and development of cutting edge cathode materials and 2) wastewater treatment at cathode of A-MFC. This review provides fundamental knowledge, critical constraints, current status and some insights for making A-MFC technology a reality at commercial scale operation.